Pancreatic stellate cell secretion and interleukin-6 regulate pancreatic cancer cell proliferation and epithelial-mesenchymal transition through nuclear factor erythroid-2 / Wu Yuan Seng - Wu, Yuan Seng (2017)
Pancreatic ductal adenocarcinoma (PDAC) is characterized by a desmoplastic reaction mediated primarily by pancreatic stellate cells (PSC). However, the mechanisms by which PSC promote PDAC cell proliferation and motility are still unclear. Nuclear factor erythroid 2 (Nrf2), highly expressed in PDAC cells, is a transcription factor responsible for maintaining redox homeostasis. It was reported to regulate metabolic reprogramming recently and induces epithelial-mesenchymal transition (EMT) to promote tumor metastasis. The present study examined whether PSC secretory factors activate metabolic reprogramming to promote cell proliferation, and EMT via intracellular Nrf2 signaling. PSC-conditioned medium (PSC-CM) increased PDAC cell proliferation and elevated Nrf2 expression, enhancing Nrf2-regulated antioxidant genes expression through greater DNA binding. NRF2 downregulation reduced PSC-mediated PDAC cell proliferation whereas overexpression of NRF2 activity significantly increased, with PSC-CM treatment further enhanced this effect. These data strongly suggest that Nrf2 activity is required for PSC-mediated PDAC cell proliferation. PSC treatment also enhanced PDAC metabolic genes expression related to pentose phosphate pathway (PPP), glutaminolysis, and glutathione biosynthesis. This led to increased levels of ribose 5-phosphate (R5P), inosine 5’-monophosphate (IMP), glutamate, and malate metabolites in PSC-CM treated cells. Abrogation by G6PD inhibition indicated that PSC activates PPP to promote PDAC cell proliferation. Identification of PSC secretory factors that mediate these phenotypes showed that GRO-α was the most abundant cytokine, followed by IL-6 and SDF-1. Only recombinant protein IL-6 and SDF-1α significantly induced PDAC cell proliferation (~150%), and upregulated NRF2 and its target genes (AKR1C1 and NQO1). IL-6 neutralization most strongly reduced cell proliferation (~50%) compared to SDF-1α. These indicated that IL-6 and SDF-1α secreted from PSC mediate PDAC cell proliferation via Nrf2 signaling activation. It was reported that IL-6 is important for iv PDAC progression. Hence, the expression of IL6 and its receptor (IL6R) were determined in PSC and PDAC cells (AsPC-1, BxPC-3, and Panc-1). Panc-1 cells were used to study IL-6 signaling in PSC-PDAC interaction because Panc-1 expressed the lowest IL6 and highest IL6R levels. IL-6 neutralization reduced Panc-1 cell proliferation and Nrf2-induced metabolic genes. IL-6 neutralization caused PSC-induced mesenchymal to epithelial morphologic transition, and reduced the migration and invasion capacity; these were restored by tBHQ. Concurrently, upregulation of the mRNA levels was observed for CDH2, VIM, FN1, COL1A1, SIP1, SNAIL, SLAUG, and TWIST2 genes, but not for epithelial marker CDH1 encoding E-cadherin. NRF2 mRNA was upregulated in IL-6-treated PDAC cells, indicating that Nrf2 mediates PSC-induced EMT and metabolic genes via Nrf2. Furthermore, inhibition of Stat3 signaling upregulated E-Cadherin while downregulated CDH2, VIM, FN1, COL1A1, SIP1, SNAIL, SLUG, and TWIST2, NRF2 and Nrf2 target genes (AKR1C1 and NQO1). Stat3 inhibition further suppressed Nrf2-mediated EMT-related gene expression. Therefore, PSC-secreted IL-6 promotes PDAC cell proliferation via Nrf2-mediated metabolic reprogramming, and induces EMT via Stat3/Nrf2 signaling. Targeting activated Stat3/Nrf2 pathways downstream of IL-6 might provide a novel therapeutic option to improve the prognosis of patients with PDAC.